An Algorithm of PWM Modulation under Low Switching Frequency - LIU Liangjie; LIU Yong; GUO Wei; WANG Wentao; WANG Yongtong (Kongzhi Yu Xinxi Jishu)
The switching frequency of high power inverters is extreme low, so that the harmonic of PWM is very large. For solving the problem, a PWM modulation algorithm under low switching frequency was analyzed and studied, and the Matlab simulations and experiments were implemented for the optimized pulse pattern. The results indicate that the pulse pattern has excellent output, and can reduce input and output harmonics combined with specific control algorithm.